Synergistic Zoning and Management Strategies for Ecosystem Service Value and Ecological Risk at the County Level: A Case Study of Songzi City, Hubei Province, China - Tingting Han; Jing Luo; Yilin Gan; Yaru Sun; Lingling Tian (Land)
Counties are fundamental units for ecological restoration, where scientifically delineated zoning is essential for resource allocation and governance. This study proposes a dual-dimensional, multi-source ecological zoning framework combining ecosystem service value (ESV) and Comprehensive Ecological Risk Index (CERI), with the CERI incorporating endogenous, exogenous, and regulatory ecological risk, providing a holistic representation of county-level ecological risk mechanisms. A Self-Organizing Map (SOM) neural network model clusters ESV and CERI, identifying spatial conflict zones and enabling high-resolution ecological management unit delineation. The results indicate the following: (1) The total ESV of Songzi City amounts to CNY 7.64 billion, showing spatial heterogeneity high-value clustering and low-value dispersion pattern, and water bodies and woodlands contributing 49.17% and 29.61%, respectively. (2) The spatial distribution of CERI is high in the central and eastern regions, and low in the west pattern, radiating from river systems under the combined effects of endogenous, exogenous, and regulatory risks. (3) Based on SOM clustering, four service clusters are identified and classified into ecological preventive conservation, vulnerability restoration, safeguard restoration, and improvement and utilization, shifting from broad-scale control to targeted ecological governance. This framework addresses the limitations of traditional single-dimensional risk assessments and provides a scientific basis for sustainable county-level ecological management.